'Hitting the glass ceiling' – gender and media management in sub-saharan africa. (7th October 2011) - ZUIDERVELD, MARIA
The aim of this study is to discuss the importance of gender in editorial leadership in African countries. Women in leading positions in the media industry work in a traditionally male-dominated area. In-depth, semi-structured interviews were carried out with five women on their work in media management in Zambia, Uganda, Nigeria and Ethiopia in order to explore how a group of female media managers in a non-western setting manage both their gendered identity and their identity as media professionals. This study challenges a western-based understanding of the role of gender in newsroom cultures. Pierre Bourdieu's concept of capital is used as an analytical instrument. The study suggests that female gender is regarded as a positive capital, which contradicts other studies of women in media management. Another conclusion is that the 'velvet ghetto' is spreading, as women in journalism receive low salaries, if any.